Attracting Diverse Talent to Academia: Perspectives of Medical Students and Residents. (October 2018) - Sánchez, Nelson F.; Poll-Hunter, Norma; Spencer, Dennis J.; Lee-Rey, Elizabeth; Alexander, Andreia; Holaday, Louisa; Soto-Greene, Maria; Sánchez, John P.
Women and underrepresented racial/ethnic minority faculty (URM) are critical to developing inclusive learning environments. Career counselors can benefit from understanding the factors influencing women's and URMs' interest in academic careers, as this population remains markedly underrepresented in academic medicine. A mixed methods study was conducted among medical students and residents yielding 643 survey and 121 focus group participants. Participants were diverse by gender and race/ethnicity. Themes included (a) factors influencing career interest, (b) influential others, (c) timing of career interest, and (d) career expectations. Findings show differences among women, URM, and dominant-identity groups. Implications include how career development programs and institutional diversity policies and practices should consider developing and offering activities that support (a) mentoring—especially for women trainees, (b) learning how to align academia and community engagement and scholarship—especially for URM trainees, and (c) senior leadership development support for women and URM trainees.